ROLE OF RASA AUSHADHIS IN PAIN MANAGEMENT - G.Sheela sravanthi; P.V.N. R Prasad (International Journal of Applied Ayurved Research, 2018)
Pain is the most common reason patients seek medical advice, everyone experiences some sort of pain at some point of time. Pain is a protective mechanism or a warning to prevent further injury. Pain is an unpleasant sensory and emotional experience associated with actual and potential tissue damage, there are many side effects to the pain killers, which are presently used. Rasa Shastra is a boon to Ayurveda where the herbal drugs which are used along with rasa aushadhis are being more potent and cost effective and quick in action. Present work has done to collect the material of Maha Rasas, Uparas, Sadarana Rasas and Visha Varga Dravyas which are having the Shulagna property and their usage in different types of pain according to different authors.